Global Trends in Research of Amino Acid Metabolism in T Lymphocytes in Recent 15 Years: A Bibliometric Analysis - Jiaona Xu; Yinan Yu; Shijie Li; Fanghui Qiu (Journal of Immunology Research)
Amino acid metabolism in T cells determines the therapeutic efficacy of T-cell-targeting drugs. To assess the direction of amino acid metabolism in T cells and construct related knowledge structure, we performed a bibliometric analysis aiming at amino acid metabolism in T cells utilizing studies publicized in recent 15 years. Three hundred thirty-seven related studies were downloaded from the Web of Science Core Collection (WoSCC), and the information on countries, institutes, and authors was collected and analyzed. In addition, the present research status and future trends were explored according to the results yielded from the analysis of cited references and keywords. This study revealed that publications regarding amino acid metabolism in T cells gradually increased each year. The USA is the top producer and most influential country in this field. Recent research has focused on the correlation between the metabolism of several amino acids and regulatory T cells (Tregs) and CD8+ T cells. Overall, this research offers a comprehensive exhibition on the field of amino acid metabolism in T cells, which will help researchers to study this domain more effectively and intuitively.